2017
DOI: 10.1177/0022002717736567
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Bearing Witness: The Impact of Testifying at War Crimes Tribunals

Abstract: Intersections exist regarding how institutions and individuals respond in the wake of mass violence, and we explore one theoretical perspective: resilience—the ability to overcome in the face of adversity. By controlling for the institutional context, we analyze the microlevel impact of testifying on witnesses who testify. New survey data provide information from 300 prosecution, defence, and Chambers witnesses who appeared at the International Criminal Tribunal for the Former Yugoslavia. We test propositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In a survey study of 300 ICTY witnesses Kimi King and James Meernik (2017;2019) found that few of the witnesses experienced re-traumatisation due to testifying. Charters and Vahidy (2009) and Stepakoff et al(2005) found that the majority of the witnesses -and particularly the victim-witnesses -in the Sierra Leone tribunal had positive experiences from testifying.…”
Section: Studies Of Victims In Trials After Gross Human Rights Violationsmentioning
confidence: 99%
“…In a survey study of 300 ICTY witnesses Kimi King and James Meernik (2017;2019) found that few of the witnesses experienced re-traumatisation due to testifying. Charters and Vahidy (2009) and Stepakoff et al(2005) found that the majority of the witnesses -and particularly the victim-witnesses -in the Sierra Leone tribunal had positive experiences from testifying.…”
Section: Studies Of Victims In Trials After Gross Human Rights Violationsmentioning
confidence: 99%
“…The greater the damage to their physical and mental well-being as a consequence of war, the more susceptible individuals become to intimidation and threats of violence (Davies 2014). While not all those who survive exist in a perilous state indefinitely, as many may be quite resilient and become motivated to speak truth to power, those who can be intimidated represent prime opportunities for targeted violence (King and Meernik 2019).…”
Section: Targeting and Violencementioning
confidence: 99%
“…These witnesses are an attractive target for those seeking to deter them from testifying because they isolate themselves and may have a limited social network (Justino 2009). Conversely, healthy coping mechanisms should help increase a witness’ resilience and provide a social support system offering protection against would-be adversaries (King and Meernik 2019). Those who seek the support of others (friends, family, religious figures, coworkers, etc.)…”
Section: Targeting and Violencementioning
confidence: 99%
“…Scholars across the disciplines have extensively examined the relative merits and faults of the witness‐driven model, highlighting concerns such as reliability and re‐traumatization, to name a few (Ciorciari and Heindel ; Combs ; Dembour and Haslam ; King et al ; Stover ). Such studies often focus on the experience of the individual witness as their object of research.…”
mentioning
confidence: 99%